Peran Tafsir Al-Qur'an dalam Mengatasi Tantangan Proses Ekonomi - Muhammad Halif Asyroful Bahana (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
Globalisation introduces substantial changes to human existence, combined with in social, economic and cultural elements. However, these adjustments furthermore offer critical obstacles, specifically for Muslims, United Nations agency generally need to confront beliefs and practices that contrast with monotheism teachings. With an emphasis on social, economic, and cultural facets, this analysis seeks to examine the applicability of Qur'anic interpretation in addressing the issues of globalization. It is intended that a wide range of flexible and conversational approaches to interpretation will provide fresh perspectives on how the holy text's lessons remain pertinent and relevant in today's modern world. Using literature reviews and material gathered from a variety of contemporary commentary, books, scientific papers, and journals, a qualitative analysis technique is employed. The findings of the analysis demonstrate that a discourse interpretation of the Qur'an will address the problems of economic injustice, social inequality, and the cultural psychological state brought on by globalization. Finally, in order to respond to the problems of globalization and ensure that the teachings of the Qur'an remain relevant in the current era, a dynamic interpretation method is absolutely essential.